Oral plasma cell granuloma: A case report of an ambiguous lesion - Manveen Kaur Jawanda; Ravi Narula; Ashutosh Nirola; Shruti Gupta; Priya Gupta (Wolters Kluwer Medknow Publications, 2014)
Plasma cell granuloma (PCG) is a rare reactive tumor such as proliferation composed chiefly of plasmacytic infiltrate. Both clinically and histopathologically, it may be misinterpreted as various pathological entities thus necessitating the complete evaluation of patient and proper histopathological and immunohistochemical analysis of the tissue to rule out other lesions with poor prognosis. Here, we present a case of PCG of gingiva in a female patient masquerading as pyogenic granuloma clinically and plasma cell neoplasms histopathologically.